Iron Deficiency in Children in Sydney - V.A. Lovric (Indonesian Pediatric Society, 1975)
Results of prospective studies of over 2,000 children with nutritional iron deficiency anaemia in Sydney are presented. The epidemiological aspects were also investigated in a study of 1500 well children, aged 6 — 36 months, attending Baby Health Centres in Sydney and the incidence of iron deficiency anaemia was found to be low (3%). Iron deficiency anaemia was common in children admitted to hospital with acute infections and diarrhoea (20%) and was clinically unsuspected in two-thirds. Because of inadequate iron prophylaxis the incidence in prematures was high (30%). Another groups recently arrived migrant children, also had a high incidence of anaemia (25%). There was circumstantial evidence linking anaemia and childhood morbidity. Matched patients awaiting elective minor surgery had a low incidence (3%) of iron deficiency anaemia, similar to the data published in out patients in Surabaya.